2017
DOI: 10.1016/j.nanoen.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Liquid cell transmission electron microscopy observation of lithium metal growth and dissolution: Root growth, dead lithium and lithium flotsams

Abstract: We present in situ environmental transmission electron microscopy (ETEM) observation of metallic lithium nucleation, growth and shrinkage in a liquid confining cell, where protrusions are seen to grow from their roots or tips, depending on the overpotential. The rate of solidelectrolyte interface (SEI) formation affects root vs. tip growth mode, with the former akin to intermittent volcanic eruptions, giving kinked segments of nearly constant diameter. Upon delithiation, root-grown whiskers are highly unstable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
389
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 417 publications
(409 citation statements)
references
References 71 publications
17
389
1
2
Order By: Relevance
“…Second, in order to apply the linear stability analysis to lithium metal batteries (LMBs), we would also need to model the solid electrolyte interphase (SEI) layer [176][177][178][179], which will certainly increase the complexity of the model but also make it more predictive. Incorporating these two aforementioned extensions into the model may help explain recent experimental studies of lithium growth that have demonstrated that competing SEI reactions and stress effects lead to root growth before Sand's time or below limiting current [93][94][95], which is different from tip growth of dendrites under transport limitation that we have focused on in this paper. Third, other chemical mechanisms for overlimiting current such as water splitting [114,115] and current-induced membrane discharge [132] may be present.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in order to apply the linear stability analysis to lithium metal batteries (LMBs), we would also need to model the solid electrolyte interphase (SEI) layer [176][177][178][179], which will certainly increase the complexity of the model but also make it more predictive. Incorporating these two aforementioned extensions into the model may help explain recent experimental studies of lithium growth that have demonstrated that competing SEI reactions and stress effects lead to root growth before Sand's time or below limiting current [93][94][95], which is different from tip growth of dendrites under transport limitation that we have focused on in this paper. Third, other chemical mechanisms for overlimiting current such as water splitting [114,115] and current-induced membrane discharge [132] may be present.…”
Section: Discussionmentioning
confidence: 99%
“…The SEI is in the focus of many processes limiting lifetime, performance, and safety of lithium-ion batteries. It affects the inhomogeneous growth and dissolution of lithium metal [6,7]. Thermal runaway as the main cause for battery failure is promoted by SEI decomposition [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The products by side reactions at the interface between electrode and SEI films. [1][2][3][4] The products by side reactions at the interface between electrode and SEI films.…”
Section: Introductionmentioning
confidence: 99%